(untitled) (diségno, 2026)
Geometry and Graphics understood both as disciplines and fundamental tools of perception, technique and thought, today embrace an increasingly complex set of research areas. In this context, the International Conference on Geometry and Graphics (ICGG) has been a relevant meeting point for the scientific community since 1978, promoting exchange between scholars, professionals and institutions involved in research on the foundations, innovations and applications of Geometry and Graphics. [read more]